The Protection of Privacy as Part of Human Rights in Indonesia and the US Law - Amos Mokoross; I Nyoman Aji Duranegara Payuse (Sociological Jurisprudence Journal, 2023)
The right to privacy is the right of every person which is a human right. Protection of privacy rights needs to be protected by the government through the resulting regulations. Protection of privacy rights is imposed on the government because of the duty to protect that must be carried out by the government. The research aim is to decsribe the protection of privacy as part of human rights in Indonesia and the US Law. In this case, the research method state that the authority to form regulations as desired. This is based on the principle of state sovereignity. The political will of a country determines how to protect the privacy rights of its citizens. The result shows that Indonesia and the United States regulate the protection of the privacy rights of their citizens at various levels of legislation. This is done by imposing the protection of privacy rights on state institutions and other entities that obtain the data by various methods. Protection of privacy rights is also carried out by providing space for remedies for people whose rights have been violated by personal data management institutions through a lawsuit mechanism to obtain compensation.